PEMBAHARUAN KEBIJAKAN HAK ASASI MANUSIA DI INDONESIA PASCA REFORMASI TAHUN 1998 - Afriyandi, Muhammad Rizcky; Ratnawati, Elfrida; Rahmawan, Dhany; Indirahati, Novina Sri; Bustani, Simona (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Post-1998 Reform Era, Indonesia has shown an increased commitment to reforming human rights (HR) policies through the enactment of various laws, such as Law No. 39 of 1999 on Human Rights, Law No. 26 of 2000 on the Human Rights Court, and Law No. 12 of 2022 on Sexual Violence Crimes. The purpose of this study is to analyze the role of these laws in providing HR protection and to identify the challenges in their implementation. The analysis shows that, despite strengthened regulations, technical challenges, varying interpretations at the regional level, and uneven public understanding remain obstacles. Additionally, globalization, which brings higher international standards, has pushed Indonesia to align its legal policies with global commitments. In conclusion, more intensive public outreach and a community-based approach are necessary to ensure optimal HR protection. Recommendations are provided to strengthen HR education among the public and to enhance inter-agency coordination for effective enforcement.Keywords: Inter-Agency, Coordination, Effective Enforcement.